(untitled) (The Macau Ricci Institute Journal, 2020)
In search of a new paradigm of economics I submit three heuristic proposals which can bring some clarity and guidance to this difficult undertaking. First, we may focus on the fundamental question of the purpose of business and the economy. Second, we place this question into the global and pluralistic context. And third, we clarify the components of which any economic system consists.